The importance of serum biglycan levels as a fibrosis marker in patients with chronic hepatitis B. Issue 5 (7th December 2016) - Ciftciler, Rafiye; Ozenirler, Seren; Yucel, Aysegul Atak; Cengiz, Mustafa; Erkan, Gulbanu; Buyukdemirci, Erkan; Sönmez, Cemile; Esendaglı, Guldal Yılmaz
Abstract : Background: Liver biopsy is recommended in the majority of patients with chronic viral hepatitis for fibrosis evaluation. Because of the potential risks of liver biopsy, many studies related to non‐invasive biomarkers of hepatic fibrosis have been performed. We aimed to assess the diagnostic value of serum biglycan as a non‐invasive fibrosis marker in chronic hepatitis B patients. Methods: This study included 120 patients with biopsy‐proven hepatitis B patients and 60 healthy controls. Fibrosis stage and necroinflammatory activity were assessed in liver biopsy specimens. Biglycan level was measured using an ELISA assay. Results: S erum biglycan levels of chronic hepatitis B patients were found to be significantly higher than those of healthy controls (337.3±363.0 pg/mL vs 189.1±61.9 pg/mL, respectively, P <.001). There was a statistically significant positive correlation between serum biglycan level and fibrosis stage ( P =.004; r =.213). Besides, a statistically significant positive correlation was found between serum biglycan level and necroinflammatory activity ( P <.001; r =.271). The AUROC of BGN levels was 0.702 for fibrosis stage, differentiating patients from healthy controls with statistical significance ( P <.001). The AUROC of BGN levels was 0.632 for necroinflammatory activity score, differentiating patients from healthy controls with statistical significance ( P =.004). Conclusions: Serum biglycan might be used as a non‐invasive marker of liver fibrosis. Further studies are needed to evaluate the usefulness of this marker.